EVALUASI PROGRAM PRAKTIK KERJA LAPANGAN (PKL) PADA KONSENTRASI KEAHLIAN TEKNIK MEKANIK INDUSTRI DI SMKN 8 KOTA SERANG - Andhika, Muhamad Bintang Putra; Atep Iman; Deddy Supriyatna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to evaluate the effectiveness of the Practical Work Program (Praktik Kerja Lapangan/PKL) implementation in the Industrial Mechanical Engineering Skills Concentration at SMKN 8 Kota Serang. The evaluation was conducted because PKL is a strategic component of vocational education, yet its effectiveness needs to be continuously assessed to ensure alignment with industry demands and competency achievement. This research employed a quantitative descriptive approach using the CIPP evaluation model (Context, Input, Process, Product). The participants consisted of 31 twelfth-grade students who completed PKL. Data were collected using a Likert-scale questionnaire that had passed validity testing (25 valid items) and reliability testing with Cronbach’s Alpha of 0.909. Data analysis was performed descriptively by calculating mean scores and categorizing the results based on predetermined criteria. The findings indicate that the overall implementation of the PKL program was categorized as Very Good. In the Context aspect, the program objectives were considered relevant to industry needs. The Input aspect showed adequate readiness of students and supporting resources. The Process aspect reflected that PKL implementation and monitoring were generally conducted according to procedures. The Product aspect demonstrated positive contributions to students’ hard skills, soft skills, and work readiness. These results suggest that the PKL program has been effectively implemented and can be maintained with continuous improvement in monitoring to ensure more consistent competency development among students.